PENGARUH PERSEPSI ATRIBUT PRODUK TERHADAP MINAT BELI KONSUMEN MOBIL MEREK ISUZU ELF STUDI PADA PT. KARYA ZIRANG UTAMA ISUZUSEMARANG - Kristiana, Nela; Wahyudin, Nanang (STIE Totalwin Semarang, 2012)
This research aims to find out that do price, brand, and product quality influence consumerâs purchase interest of Isuzu Elf car brand, and also to analyze the most dominant factor in influencing consumerâs purchase interest of Isuzu Elf car brand in PT. Karya Zirang Utama Semarang. In the research, research population refers to all consumers in PT. Karya Zirang Utama Isuzu Semarang. The samples of the research are 44 respondents by using purposive sampling technique. Based on the researchâs result, concluded that regression equality is as follow: Y = 0,130 + 0,249 X1 + 0,279 X2 + 0,359 X3 + e. According to statistic data analysis, the indicators in the research are valid and the variables are reliable. On classic assumption test, free multikolonieritas regression model, heteroskedastisitas is not happened, and it is distributed normally. The sequence is individually from each variable, and the most influential variable is product quality variable with regression coefficient 0,359, then brand variable with regression coefficient 0, 279, whereas the lowest influential variable is price with regression coefficient 0,249. The model equality has value as F counts 31,348 and with significance level 0,000, where F counts bigger than F table (2, 85) and with smaller significance level than Î± (0, 05), while value of T table 1,685 because T counts > T table then Ho is rejected and Ha is accepted. It shows that variable independent in the research influential partially of dependent variable that is purchase interest. Karya Zirang needs to maintain the product quality and able to create new products with better quality, in order to can compete with another brand of diesel car